The Encyclopedia of philosophy - Edwards, Paul, 1923-2004. (New York : Macmillan Publishing Co. , Inc & The free Press, 1967)
Treats eastern & western philosophy; it deals with ancient, medieval and modern philosophy; and it discusses the theories of mathematicians, physicist, biologist, sociologists, psychologists, moral reformers and religious thinkers where these have had an impact on philosophy
v. 1-2, Abbagnano to entropy (1 v. ) -- v. 3-4. Epictetus to logic (1 v. ) -- v. 5-6. Logic to psychologism (1 v. ) -- v. 7-8. Psychology to Zubiri; Index (1 v. )
Includes bibliographical references and index
Keywords: Philosophy -- Dictionaries; Dictionaries